Edge Detection with Sub-pixel Accuracy Based on Approximation of Edge with Erf Function - Hagara, Miroslav; Kulla, Peter (Společnost pro radioelektronické inženýrství, 2011)
Edge detection is an often used procedure in digital image processing. For some practical applications is desirable to detect edges with sub-pixel accuracy. In this paper we present edge detection method for 1-D images based on approximation of real image function with Erf function. This method is verified by simulations and experiments for various numbers of samples of simulated and real images. Results of simulations and experiments are also used to compare proposed edge detection scheme with two often used moment-based edge detectors with sub-pixel precision.
Keywords: Edge detection; sub-pixel accuracy; image processing